School drop-out in urban high schools in Argentina: New indicators for planning education inclusion policies - Steinberg, Cora (Education Policy Analysis Archives, 2014)
Argentina has assumed the commitment that adolescents and youth complete secondary level education. While the access to this level has increased significantly throughout the recent years, there are still some serious problems that prevent us from reaching that goal. Compulsory secondary school constitutes an important challenge for the educational system. In addition to appealing to accessibility of material resources to expand the offer of education, it requires that we fundamentally address the school’s institutional culture, the actors involved, and the pedagogic proposal for this level. School dropout is undoubtedly the most critical point in this assessment. This study aims to expand the diagnosis of the dropout crisis that takes place during the academic year in the secondary schools in Argentina. The analysis focuses on state secondary schools in urban areas, considering the territory, and the configuration of its offer. Do the same dropout levels take place in all the state secondary schools of the country? Based on the analysis of dropout levels for each secondary school and the dispersion of this phenomenon observed depending on its distribution across schools the results of this study indicate that it is possible to identify different situations. The results show that there are at least four types of scenarios which require different political strategies. They warn about the level of heterogeneity present in the educational offer of this level in each of the territories and call for a deeper analysis of this issue with more information about the social and institutional context of the schools.